Penentuan Fasies dan Arah Arus Purba Berdasarkan Karakteristik Batuan Dan Struktur Sedimen Slump di Desa Ngleses, Kecamatan Juwangi, Kabupaten Boyolali, Jawa Tengah - rizqi, al hussein flowers; Timotius Tuska, Robert; Fajar, Ari; Rusmania Ramadhani, Saviola (ReTII, 2025)
The research location is in the Ngleses area, Juwangi District, Boyolali Regency, Central Java. The research location is in the Kendeng Zone and is included in the Kerek Formation. This study uses the Measuring Section method or rock profile using a meter. The purpose of this study is to determine the facies and direction of ancient currents based on the characteristics of the rocks and sediment slump structures found at the research site. From the field data that has been observed, there are 5 types of constituent rocks found at the research site, namely, limestone, sandstone, napal, napal, and carbonate sandstone. From the measurement of the Measuring Section or rock profile, it was found that the interplay of navel and clastic limestone of medium sand size at the bottom, followed by massive limestone, and carbonate sandstone at the top with a slump sediment structure. From the results of the measurement of the Measuring Section or rock profile, 3 deposition facies were obtained starting from the Classical Turbidite (CT) facies at the bottom, the Massive Sandstone (MS) facies in the middle, and the Slump Facies (SL) at the top. Based on the results of the rosset diagram, it was found that the ancient current pattern at the research location had a Bipolar pattern. The sediment slump structure found at the research site has a direction of N 182 ( E, from the slump sediment structure data can be interpreted as the direction of the ancient flow of the research location is north-south, and the source of sediment material that then forms rocks at the research site has a source from the north. Keyword : Facies, Paleocurrent, Slump Structures